Dinamika Interaksi Antarbudaya di Media Sosial (Analisis Perbedaan Bahasa, Simbol, Nilai, dan Norma serta Dampaknya terhadap Kesehatan Mental Mahasiswa Multikultural) - Galih Geraldi Primayana; Riastri Novianita; Cindya Yunita Pratiwi; Selvy Maria Widuhung (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze the dynamics of intercultural interactions on social media, particularly differences in language, symbols, values, and norms, and their impact on the mental health of multicultural students. A qualitative approach using library research methods was used to understand the dynamics of intercultural interactions on social media and their impact on the mental health of multicultural students. Data were collected through literature reviews from books, journals, research reports, and credible online sources related to intercultural communication, social media, digital literacy, and mental health. The analysis was conducted systematically using content analysis and thematic analysis to identify key themes and synthesize the findings into a comprehensive and holistic analytical framework. The results show that intercultural interactions on social media are complex and influenced by differences in language, symbols, values, and norms of multicultural students. These interactions have a dual impact on psychological well-being, both expanding intercultural understanding and tolerance and causing stress, anxiety, isolation, and self-dissatisfaction if differences are not managed properly. Students' abilities to adapt, understand the communication context, and build positive social support have proven crucial for creating harmonious, inclusive, and supportive interactions in the digital environment.